Postural-respiratory function of the diaphragm assessed by M-mode ultrasonography - Martin Sembera; Andrew Busch; Alena Kobesova; Barbora Hanychova; Jan Sulc; Pavel Kolar (PLoS ONE, 2022)
Objectives The diaphragm changes position and respiratory excursions during postural loading. However, it is unclear how it reacts to lifting a load while breath-holding or breathing with simultaneous voluntary contraction of the abdominal muscles (VCAM). This study analyzed diaphragm motion in healthy individuals during various postural-respiratory situations. Methods 31 healthy participants underwent examination of the diaphragm using M-mode ultrasonography, spirometry, and abdominal wall tension (AWT) measurements. All recordings were performed simultaneously during three consecutive scenarios, i.e., 1. Lifting a load without breathing; 2. Lifting a load and breathing naturally; 3. Lifting a load and breathing with simultaneous VCAM. Results Using paired-samples t-tests, lifting a load without breathing displaced the diaphragm’s expiratory position more caudally (P < .001), with no change noted in the inspiratory position (P = .373). During lifting a load breathing naturally, caudal displacement of the diaphragm’s inspiratory position was presented (P < .001), with no change noted in the expiratory position (P = 0.20) compared to tidal breathing. Total diaphragm excursion was greater when loaded (P = .002). Lifting a load and breathing with VCAM demonstrated no significant changes in diaphragm position for inspiration, expiration, or total excursion compared to natural loaded breathing. For all scenarios, AWT measures were greater when lifting a load (P < .001). Conclusion In healthy individuals, caudal displacement and greater excursions of the diaphragm occurred when lifting a load. The postural function of the diaphragm is independent of its respiratory activity and is not reduced by the increase in AWT.